Iodine-catalyzed oxidative cross-coupling of indoles and azoles: Regioselective synthesis of N -linked 2-(Azol-1-yl)indole derivatives - Danupat Beukeaw (2018)
© 2015 American Chemical Society. A highly efficient iodine-catalyzed regioselective oxidative cross-coupling of an indole C-H bond and azole N-H bond is described. This metal-free reaction can be easily carried out at room temperature under mild and environmentally friendly conditions and provides a series of N-linked 2-(azol-1-yl)indole derivatives in moderate to excellence yields.